RIS-Assisted Spatial Modulation with Hybrid Distortions for Terahertz Communication - Singh A.; Kumar M.H.; Sharma S.; Bhatia V. (My University, 2025)
Terahertz (THz) band communication and reconfigurable intelligent surface (RIS) have emerged as promising technologies for next-generation wireless networks. In this paper, RIS-assisted THz system using spatial modulation (SM) transmission method is analyzed, and it is referred to as RIS-assisted SM THz (RSMT) system. The proposed RSMT system achieves higher energy and spectral efficiencies due to RIS and SM techniques. Further, imperfections of THz devices such as in-phase/quadrature imbalance and nonlinearity considered as hybrid distortions, have analyzed in the RSMT system. Impact of system parameters such as number of transmitting and receiving antennas, modulation order, and RIS beamforming is analyzed under hybrid distortions. Numerical results of symbol error rate (SER) and sumrate show that the RIS beamforming enhances performance of the RSMT significantly as compared to the conventional THz system without RIS. © 2022 IEEE.